Program Vaksinasi Covid 19 di Kelurahan Tebing Okura Kecamatan Rumbai Timur Pekanbaru - Faridhi, Adrian; Fahmi, Sudi; Suprayoga, Tatang (Universitas Nusantara PGRI Kediri, 2022)
The national vaccination program is the main agenda of the Government to suppress the spread of Covid 19 in Indonesia, the Government issues regulations or laws and regulations to provide a legal basis for implementing the national Covid 19 vaccination policy, Massive socialization of vaccinations at the national level to the village level is a reference for the distribution of Covid 19 vaccinations, Tebing Tinggi Okura Village is intensively vaccinating for the sake of high vaccination in Pekanbaru City, dealing with misleading information about Covid 19 vaccination, so partners who are residents of Tebing Tinggi Okura Village, Rumbai Timur District, Pekanbaru City need information about the national vaccination program along with its legal basis and legal consequences that accompanies the Covid 19 vaccination program. The approach methods offered to resolve the problems of program partners that have been mutually agreed upon within the program realization period are lectures, dialogues and guidance conducted using online media or directly depending on the Covid 19 pandemic. As a result of the service, the community has an increased understanding of the obligation to participate in the Covid 19 national vaccination program, as well as the accompanying sanctions for people who are determined to be vaccine recipients, but do not participate in the vaccination.